De schoen van Jan Jansen - Goudsmit, Lisa (Rotterdam : Nai010, 2012)
Jan Jansen (b. 1941) has been turning heads with his voluptuous, baroque and experimental footwear for more than 40 years. He made his international breakthrough in 1973 with his now world-famous bamboo shoe, an icon beloved by fashion and art lovers alike. In this publication author Lisa Goudsmit looks at the bamboo shoe as fashion item and art object and relates how this shoe design grew into an icon. The book also highlights other designs in Jan Jansen's extensive oeuvre. In addition, Goudsmit examines Prada's notorious 2005 copy, which Jansen cynically dubbed 'an affectionate adoption', and the possible impact of this copy on the image of both the shoe and of the designer. Lisa Goudsmit is a design historian and fashion journalist, with a special interest in the intersection of fashion, design and art.
Teksten in het Engels en Nederlands.
boek
Keywords: Jansen, Jan